2016
DOI: 10.1002/jcsm.12131
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid obesity, but not nutrition, prevents critical illness‐induced muscle wasting and weakness

Abstract: BackgroundThe ‘obesity paradox’ of critical illness refers to better survival with a higher body mass index. We hypothesized that fat mobilized from excess adipose tissue during critical illness provides energy more efficiently than exogenous macronutrients and could prevent lean tissue wasting.MethodsIn lean and premorbidly obese mice, the effect of 5 days of sepsis‐induced critical illness on body weight and composition, muscle wasting, and weakness was assessed, each with fasting and parenteral feeding. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 51 publications
2
70
0
3
Order By: Relevance
“…53,54 Skeletal muscle density has been suggested to be an independent marker of clinical outcome. 66 Low levels of testosterone or vitamin D were not prognostic for muscle mass and function in middle-aged and elderly men, while low insulin-like growth factor 1 (IGF-1) levels were found to predict alterations in gait speed in men aged ≥70 years. 34 Another contributing factor to sarcopenia is a variable degree of malnutrition 56 that may be caused by inflammatory cytokines, 57-59 which have been known to contribute to anorexia in chronic disease.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 97%
See 1 more Smart Citation
“…53,54 Skeletal muscle density has been suggested to be an independent marker of clinical outcome. 66 Low levels of testosterone or vitamin D were not prognostic for muscle mass and function in middle-aged and elderly men, while low insulin-like growth factor 1 (IGF-1) levels were found to predict alterations in gait speed in men aged ≥70 years. 34 Another contributing factor to sarcopenia is a variable degree of malnutrition 56 that may be caused by inflammatory cytokines, 57-59 which have been known to contribute to anorexia in chronic disease.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 97%
“…65 Interestingly, premorbid obesity, but not exogenous macronutrients, attenuated muscle wasting in critical illness. 66 Low levels of testosterone or vitamin D were not prognostic for muscle mass and function in middle-aged and elderly men, while low insulin-like growth factor 1 (IGF-1) levels were found to predict alterations in gait speed in men aged ≥70 years. 67 A recent study has identified low testosterone in men as an independent risk factor in CHF.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 97%
“…Recently, premorbid overweight/obesity has been shown to protect against muscle wasting and weakness in both critically ill patients and in septic mice [15]. In these septic mice, the overweight/obese preserved their muscle mass while losing fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…Hierbei legen Studiendaten zu verschiedenen Erkrankungen nahe, dass ein höherer BMI mit einer geringeren Mortalität assoziiert ist, z. B. beim Myokardinfarkt und bei der Sepsis [7,8]. Allerdings werden diese Studien methodisch angegriffen, insbesondere da es sich in der Regel um reine Beobachtungsstudien handelt, Confounder wie Tabakkonsum nicht ausreichend berücksichtigt werden oder eine unbewiesene Kausalität postuliert wird [9,10].…”
Section: Das Adipositas-paradoxonunclassified